Tunable Flexibility and Porosity of the Metal-Organic Framework DUT-49 through Postsynthetic Metal Exchange - Garai, Bikash; Bon, Volodymyr; Krause, Simon; Schwotzer, Friedrich; Gerlach, Martin; Senkovska, Irena; Kaskel, Stefan (Chemistry of Materials, 2020)
As a prominent and representative example of flexible metal-organic frameworks (MOFs), DUT-49(Cu) has gained attention due to the unique phenomenon of negative gas adsorption (NGA), originating from an unprecedented structural contraction during the gas adsorption. Herein, postsynthetic metal exchange is demonstrated to afford DUT-49 frameworks with a wide variety of metal cations, e.g., Mn2+, Fe2+, Ni2+, Zn2+, Cu2+, and Cd2+. The single-crystal-to-single-crystal conversion allowed characterization of the new MOFs by single crystal X-ray diffraction, indicating identical structure and topology compared with that of previously explored DUT-49(Cu) framework. This approach is proven successful in achieving Mn-Mn and Cd-Cd dimers, which are rare examples of M-M paddle-wheel SBUs. The relative stability and flexibility of the resulted frameworks are observed to be highly sensitive to the metal ion of the framework, following the trends predicted by the Irving-Williams series. DUT-49(Ni) was recognized as a second material from the DUT-49 series showing adsorption-induced transitions. A sequential increase in framework flexibility from rigid to flexible and from flexible to NGA has been achieved through selective incorporation of metal centers into the structure. Finally, heterometallic structures are formed by selective and controlled exchange of metal ions to finely tune the flexibility and NGA phenomenon of the framework.
CRIS-Team Scopus Importer:2022-04-14